Compound modification method of calcium carbonate powder and talcum powder
Through the composite modification method of calcium carbonate powder and talc powder, the microbial fermentation broth and chitosan modification treatment is used to solve the structural instability and functional imbalance of the powder material, and the efficient and uniform powder modification effect is achieved, which improves the dispersion and interface binding force of the material.
Patent Information
- Application Number
- CN202510524616.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2025-07-18
AI Technical Summary
In the prior art, functional powder materials have unstable structural instability, functional imbalance and low composite efficiency, especially in terms of particle size control and surface modification, resulting in poor dispersion, unstable adsorption rate and low material fusion.
The compound modification method of calcium carbonate powder and talc powder is adopted. By culturing microorganisms with secreted biologically active substances, using fermentation broth and natural organic matter such as chitosan for modification treatment, combined with pretreatment, compound reaction and drying steps, a stable interface modification layer is formed to enhance the dispersion and wetting of the powder.
The structural stability and functional balance of powder materials are achieved, the specific surface area, dispersion and interface bonding performance are improved, and the efficiency, uniformity and ecological security of composite materials are ensured.
Smart Images

Figure CN120329758A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of the preparation of functional powder materials, and specifically to a method for compound modification of calcium carbonate powder and talc powder. Background Art
[0002] In scenarios such as agricultural planting, environmental remediation, and water treatment, the demand for high-efficiency, stable, and well-dispersible functional powder materials is increasing day by day. Such materials often play key roles such as adsorption, slow release, or interfacial regulation, and must balance the microstructure, surface properties, and stability during use.
[0003] In the prior art, the construction of functional powders has a certain foundation. Some solutions achieve particle size control through mechanical pulverization and surface physical mixing, which is simple to operate and suitable for primary dispersion applications; there are also methods that introduce surfactants for wetting treatment to improve the dispersion performance in the short term; in addition, using cellulose derivatives or natural starch as the matrix for modification treatment can also improve the adsorption capacity of the powder and the availability of raw materials. These paths have played a certain promoting role in improving the basic performance, especially having advantages in terms of cost and process stability, so they are widely used in low-threshold industrial applications.
[0004] However, there are still some deficiencies in the prior art; firstly, the above-mentioned solutions mostly focus on surface layer regulation and lack in-depth control of the material structure. For example, although the specific surface area is increased, the problem of enhanced agglomeration often occurs; although the adsorption rate is fast, the later efficiency is unstable; some processes have rough particle size control, resulting in a greatly reduced dispersion effect and easy sedimentation and blockage after use; there are even some solutions that ignore process regulation and omit key steps such as pre-freezing and stirring, resulting in uneven compounding or structural collapse; there are also shortcomings in the selection of natural components, and most of them do not establish a stable extraction mechanism, with weak interfacial binding force and low material fusion degree. Summary of the Invention
[0005] In view of the deficiencies of the prior art, the present invention provides a method for compound modification of calcium carbonate powder and talc powder, which solves the problems of unstable powder structure, functional imbalance, and low compounding efficiency in the prior art.
[0006] To achieve the above objectives, the present invention is realized through the following technical solutions: A method for compound modification of calcium carbonate powder and talc powder, comprising the following steps: S1. Cultivate microorganisms capable of secreting bioactive substances to obtain the fermentation products required for modification; S2. Collect the cultured fermentation broth and provide bio-assisted modification components. The microorganisms in the culture secrete bioactive substances during their growth and metabolism. These components have surface activity or interfacial regulation effects and can physically adsorb or chemically bond with the surface of inorganic powders during the subsequent compounding process, thereby endowing the powders with modification activity and laying a foundation for the subsequent "bio-material interface synergistic modification". S3. Extract natural organic matter as a modification adjuvant. The soluble components in the fermentation broth can interact with the inorganic components during the compounding process to form an adsorption layer or induce interfacial rearrangement, thereby enhancing the polarity and wettability of the surfaces of calcium carbonate powder and talc powder, and improving the uniformity and stability of subsequent compounding. S4. Pretreat the calcium carbonate powder and talc powder. Natural organic matter contains a large number of functional groups such as hydroxyl and amino groups and has good complexing, chelating, and coating capabilities. Under the subsequent synergistic action with the fermentation broth, it can further modify the surface of the powder particles, improve the interfacial adhesion force and dispersibility between particles, and thereby enhance the ecological safety and processing adaptability of the composite material without introducing synthetic chemicals. S5. Compound the fermentation broth, natural organic matter with the pretreated powder, and carry out a modification reaction. The powder pretreatment helps to unify the particle size distribution, reduce the degree of agglomeration, and increase the specific surface area, which is beneficial to the uniform adsorption of subsequent modifiers. At the same time, the drying treatment can remove adsorbed water and surface free substances, avoid hydrolysis or uneven adsorption problems in subsequent reactions, and improve the modification efficiency and interfacial stability. S6. Separate and remove residual microbial impurities to obtain a pure composite product. During the compounding process, the bioactive substances in the fermentation broth bind to the powder surface through hydrogen bonds, electrostatic adsorption or coordination, and at the same time, the functional groups in the natural organic matter further coat the powder to form an ordered surface composite layer, improving the wettability, thermal stability and interfacial adhesion performance of the powder, thereby realizing the functional modification of inorganic powders. S7. Dry the composite product to obtain the final composite modified powder. This step helps to remove residual microorganisms or unreacted components, avoiding biological contamination or thermal runaway problems during subsequent use. At the same time, it ensures the purity and product stability of the composite modified powder, laying a foundation for final drying and application.
[0007] Preferably, the cultivation step of the microorganisms includes: Select Bacillus strains with a weight fraction of 1 - 3 parts as fermentation strains. Bacillus can produce a variety of functional biomolecules during growth, including sugars, proteins, and surface-active peptides. These substances have good adsorption and modification activities and can adsorb, complex, or crosslink in the middle layer with the surface of inorganic particles, thereby constructing a "bio-inorganic" interface composite layer, which is the key biological factor for subsequent modification reactions. The components contained in the culture medium are prepared according to the following parts by weight: 15-25 parts of glucose, 2-5 parts of ammonium chloride, and 100-120 parts of water. By setting the appropriate range of carbon source and nitrogen source, the microbial metabolic pathway can be precisely regulated, making it more inclined to produce extracellular products rather than intracellular biomass accumulation, and enhancing the concentration and quality of the modified components. In addition, the regulation of water content has an important impact on maintaining the pH buffer of the system, the solubility of substances, and the suspended state of the bacteria, and is the physical carrier to ensure efficient metabolism; The inoculation amount is 3-7% of the total amount of the culture system. The inoculation ratio within this range is conducive to controlling the growth rate of the microbial population, avoiding inhibitory feedback caused by too rapid product formation, ensuring the consistency of gene expression among strains, and improving the extracellular secretion efficiency, thereby providing guarantee for obtaining stable and highly reproducible fermentation broth components; Control the culture temperature at 20-40 °C, the pH value at 6.5-7.5, and the culture time at 45-55 hours. By culturing under these conditions, the expression and secretion efficiency of extracellular modification factors can be maximized, making the fermentation broth have good modification performance. In addition, the control duration of 45-55 hours avoids product degradation or bacterial aging, and helps the stability of the subsequent reaction system.
[0008] Preferably, the steps for collecting the fermentation broth include: Centrifuge at 2500-3500 rpm for 8-12 minutes to remove the bacteria. The centrifugation process relies on the action of centrifugal force, so that microbial cells and larger solid particles are effectively separated due to density differences. At a rotational speed of 2500-3500 rpm, heavier particles such as bacteria settle to the bottom of the container, while the lighter liquid components (including fermentation products and dissolved substances) remain on the upper layer. This process not only removes the bacteria, but also avoids potential contamination of the powder by microbial residues during subsequent modification, thus ensuring the purity of the composite product; Take the supernatant and filter it through a 0.35-0.55 μm microporous membrane. The 0.35-0.55 μm membrane has good filtration accuracy, can effectively remove small particles, bacterial fragments and other impurities in the fermentation broth, and retain water-soluble active substances (such as proteins, enzymes, low molecular compounds, etc.). This filtration process further improves the purity of the fermentation broth, provides a more uniform and stable liquid basis for subsequent modification reactions, and avoids interference from fine impurities to the surface modification of the powder; Retain the filtrate as the subsequent modification component. The filtered liquid retains the active substances secreted by the microorganisms, which may include enzymes, metabolites, natural polysaccharides, etc. They have specific surface activity or biocompatibility, and can adsorb, crosslink or functionalize and modify the inorganic powder. These biomolecules can form a modified layer on the surface of the powder, improving the dispersibility, wettability, interfacial affinity and overall performance of the powder.
[0009] Preferably, the extraction steps of the natural organic matter include: 5-15 parts of chitosan are selected as the natural organic matter. The main components of chitosan are glucosamine and aminoglucose, which have strong hydrophilicity and biocompatibility. Its functional groups such as amino and hydroxyl groups can form ionic bonds or hydrogen bond interactions with the surface of inorganic particles (such as calcium carbonate powder and talc powder), helping to modify the surface characteristics of the powder, improving its dispersibility and surface affinity, and thus enhancing the performance of the powder. In the modification reaction, the cross-linking effect of chitosan contributes to the stability of the modified layer; The natural organic matter is added to 90-100 parts of water and extracted at 60-80 °C for 1-3 hours. Controlling the temperature at 60-80 °C helps the polymer chains in chitosan to unfold, increasing its contact area with solvent molecules, thereby improving the extraction efficiency. Too high a temperature may cause the degradation of chitosan, while too low a temperature results in poor extraction effect. Therefore, 60-80 °C is an ideal extraction temperature. Water as a solvent serves to release the soluble components of chitosan and also helps it to be evenly distributed in the subsequent composite process; After filtration through a 150-250 mesh filter cloth, it is used for the composite reaction. The 150-250 mesh filter cloth can effectively remove solid particles and insoluble substances in the extract, ensuring that only the effective components in the dissolved state (such as dissolved chitosan) can enter the subsequent composite reaction. This can avoid the coverage of the powder by larger particles or impurities in the composite reaction or incomplete reaction, ensuring the uniformity and effect of the modification process.
[0010] Preferably, the pretreatment steps of the calcium carbonate powder and talc powder include: The calcium carbonate powder and talc powder are mixed in a mass ratio of 1:1, with each being 50-60 parts. The 1:1 mass ratio helps to achieve the uniform distribution of calcium carbonate and talc powder in the modification reaction. Calcium carbonate has excellent filling properties and good reinforcing effects, while talc powder has good lubricity, thermal stability, and anti-caking properties. After being mixed in proportion, it not only helps to improve the dispersion uniformity of the composite material but also enables complementary physical and chemical properties, thereby forming a uniform and stable functional interface layer in the subsequent modification; Sieved through a 150-250 mesh sieve. Through this sieving step, larger particles and agglomerates generated due to the electrostatic action of the powder can be removed. The sieved fine particles have a larger specific surface area and a more uniform particle size distribution, which not only provides a more sufficient reaction interface for the subsequent composite modification but also improves the uniformity of the modification effect. In addition, the refined powder particles are beneficial for full contact with the fermentation broth and chitosan solution, improving the binding effect of surface active groups; Dry at 70 - 80 °C for 7 - 9 hours until the moisture content is <1%. The surfaces of calcium carbonate and talcum powder are prone to adsorbing moisture in the air. If the water content is too high, unnecessary moisture will be introduced during the subsequent compound modification process, affecting the reaction efficiency. Therefore, the drying temperature of 70 - 80 °C can effectively remove the moisture on the surface and in the pores of the powder, while not causing thermal decomposition or crystal structure changes of the powder. Controlling the drying time of 7 - 9 hours ensures that the internal moisture of the powder is fully volatilized, reducing the final moisture content to below 1%, which helps to improve the surface activity of the powder and provide a more stable reaction matrix for the subsequent compound modification reaction.
[0011] Preferably, the compound treatment step includes: Mix 8 - 12 parts of fermentation broth, 3 - 7 parts of natural organic matter extract, and 90 - 110 parts of the pretreated calcium carbonate - talcum powder mixture. The enzymatic action of the fermentation broth and the chemical adsorption of the natural organic matter extract act together to form a modified layer on the powder surface, significantly improving the surface properties of the powder. At the same time, controlling the proportion of calcium carbonate and talcum powder within the range of 90 - 110 parts can ensure the uniformity of the composite material, improving the physical properties, wettability, and dispersion stability after compound modification; Stir - react in a reaction kettle under atmospheric pressure. The reaction temperature is 25 - 35 °C, the stirring rate is 150 - 250 rpm, the reaction time is 2 - 4 hours, and the pH value is controlled at 6 - 7. 25 - 35 °C is the optimal reaction temperature for enzyme activity and natural organic matter, avoiding enzyme inactivation or chitosan degradation caused by too high temperature, and at the same time promoting the binding of functional factors in the fermentation broth to the powder surface; The stirring speed of 150 - 250 rpm can not only effectively disperse the powder, preventing particle aggregation, but also promote sufficient contact between the fermentation broth, natural organic matter, and the powder surface, improving the reaction efficiency; 2 - 4 hours is the optimal time required to form a stable modified layer, ensuring the completion of the reaction without causing excessive reaction or by - product generation; Maintaining the pH at 6 - 7 can maximize the activity of the fermentation broth and natural organic matter, enabling the modification reaction to proceed under mild conditions and ensuring the stable formation of the modified layer on the powder surface.
[0012] Preferably, the separation step includes: Remove the residual microorganisms in the reaction by centrifuging at 2500 - 3500 rpm for 8 - 12 minutes. The centrifugal speed of 2500 - 3500 rpm is sufficient to remove most of the bacteria, while avoiding particle aggregation or loss of the target product caused by too high a rotation speed; 8 - 12 minutes ensures the complete sedimentation of the bacteria and reduces the microbial residue in the supernatant, thus reducing the burden on the subsequent filtration step; Further filtration is carried out using a filter cloth with a filtration pore size < 5 μm. A filter cloth pore size less than 5 μm can ensure that only the target product with smaller particle size and uniform dispersion is retained in the filtrate, while effectively removing tiny impurities that affect product purity, improving the purity of the composite product. Since there may still be a small amount of microorganisms or fine particles remaining in the supernatant after centrifugation, fine filtration through the filter cloth can improve the purity of the composite product and provide a clean reaction system for subsequent solid collection; The solid in the filtrate is collected as the composite product. Due to the formation of a stable organic-inorganic composite layer in the composite reaction, the surface of the obtained solid has higher hydrophilicity, dispersibility, and adsorption properties, which provide more excellent physical and chemical properties for its subsequent applications (such as plastic reinforcement, rubber filling, etc.).
[0013] Preferably, the drying step includes: Adopting the freeze-drying method; Pre-freezing at -25 to -40 °C for 1 - 3 hours. Pre-freezing is one of the key steps in freeze-drying. By quickly freezing the water in the composite modification liquid at -30 °C, fine and uniform ice crystal structures can be formed. These ice crystals can be removed more uniformly during the subsequent sublimation process, preventing the formation of large holes or uneven drying areas. Pre-freezing can fix the distribution state of powder particles in the solution, preventing particle agglomeration or movement, thereby retaining the integrity of the powder surface modification layer; Drying for 8 - 12 hours in a vacuum environment of 0.01 - 0.02 MPa to obtain dry composite powder. The vacuum condition of 0.01 - 0.02 MPa can significantly reduce the boiling point of water, thereby realizing the sublimation of ice crystals under low-temperature conditions. In a vacuum environment, water molecules directly sublimate and escape from solid ice crystals in the gaseous form without passing through the liquid phase, avoiding the dissolution and redistribution of water to the powder, thereby maintaining the integrity of the powder's microstructure and surface modification layer. The drying time of 8 - 12 hours can ensure the complete removal of water inside the powder. Especially for the organic substances and biomolecules encapsulated in the composite modified powder, due to their strong water-binding ability, sufficient sublimation time is required to completely dehydrate them.
[0014] Preferably, the composite reaction is mixed by a high-shear emulsifier with an emulsification speed of 2,500 - 3,500 rpm and an emulsification time of 20 - 40 minutes. Under the action of the shearing force of high-speed rotation, the high-shear emulsifier can fully mix the liquid phase (fermentation broth, chitosan extract) and the solid phase (mixed powder of pretreated calcium carbonate powder and talc powder), and form fine and uniform liquid droplets or suspended particles, thereby increasing the contact area of the two-phase interface. The emulsification speed of 2,500 - 3,500 rpm is sufficient to form a stable liquid-solid interface, enabling the active ingredients in the fermentation broth and chitosan extract to be evenly distributed on the surface of the powder and form a dense modified layer, thus significantly improving the interfacial wettability and dispersibility of the composite powder. Under the shearing action for 20 - 40 minutes, functional molecules in chitosan and the fermentation broth can form a uniform and stable functionalized modified layer on the surface of calcium carbonate and talc through electrostatic adsorption, hydrogen bonding, complexation, etc. This modified layer not only improves the wettability and dispersibility of the powder, but also enhances its interfacial bonding force with the matrix material.
[0015] Preferably, the particle size of the composite modified powder is controlled such that D90 ≤ 15 μm, and its specific surface area > 8 m 2 / g. The particle size distribution directly affects the dispersibility, filling property, and interfacial bonding performance of the powder. Controlling D90 ≤ 15 μm means that most powder particles have reached the level of micro-refinement, which can provide a larger specific surface area and be evenly distributed in the composite material or functional material, thereby enhancing the interfacial bonding force and improving the overall performance of the composite material.
[0016] The present invention provides a method for composite modification of calcium carbonate powder and talc powder. It has the following beneficial effects: 1. The present invention uses chitosan as a natural organic extraction component, strengthening the complexation and adsorption ability on the material surface. It achieves the effects of enhancing interfacial activity and improving adsorption efficiency. Compared with the existing technology that only relies on the regulation of surface functional groups, it solves the problems of uneven distribution of active sites and non-sustained function release.
[0017] 2. The present invention introduces a "pre-freezing - vacuum drying" linkage process to form a micro-porous structure and stabilize its morphology. It realizes the effect of loose powder structure and stable control of specific surface area. Compared with the traditional hot air drying method that cannot effectively retain the pore structure, it overcomes the technical bottlenecks of serious agglomeration and large fluctuations in specific surface area.
[0018] 3. By controlling the particle size within D90 ≤ 15 μm, the present invention effectively improves the dispersibility and uniform distribution of the product. It achieves the effects of reducing the sedimentation rate and improving the system stability. Compared with the problems of rough particle size control and easy sedimentation of products in the existing technology, this solution ensures the rheological properties and use adaptability of the final preparation.
[0019] 4. The present invention introduces constant-speed stirring and precise pH control in the compounding step to achieve sufficient contact and synergistic reaction between substances, obtaining a composite product with uniform structure and high reaction efficiency. Different from the technical methods with unstable conventional stirring conditions or lack of pH control, it successfully avoids the problems of insufficient local reaction and incomplete composite. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a flowchart of the method of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0021] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the drawings in the specification of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0022] Please refer to the attached Figure 1 : Example 1: 1. Microbial culture: Fermentation strain: Bacillus, 2 parts are used.
[0023] Medium formula: Glucose: 20 parts; Ammonium chloride: 3 parts; Water: 110 parts; Inoculation amount: 5%.
[0024] Cultivation conditions: Temperature: 35 °C; pH: 7.0; Cultivation time: 50 hours.
[0025] 2. Fermentation broth collection: Centrifugation speed: 3000 rpm; Centrifugation time: 10 minutes; Filter membrane pore size: 0.45 μm.
[0026] 3. Extraction of natural organic matter: Chitosan dosage: 10 parts; Water dosage: 95 parts.
[0027] Extraction conditions: Temperature: 70 °C; Extraction time: 2 hours; Filtration: Filter using a 200-mesh filter cloth.
[0028] 4. Pretreatment of calcium carbonate powder and talc powder: Calcium carbonate powder and talcum powder are mixed in a ratio of 1:1, with 55 parts each. Sieving specification: 200-mesh sieve.
[0029] Drying conditions: Temperature: 75 °C; Time: 8 hours.
[0030] 5. Composite treatment: Fermentation broth: 10 parts; Natural organic matter extract: 5 parts; Powder after pretreatment: 100 parts.
[0031] Reaction conditions: Temperature: 30 °C; Stirring rate: 200 rpm; Reaction time: 3 hours; pH: 6.8.
[0032] 6. Separation step: Centrifugation speed: 3000 rpm; Centrifugation time: 10 minutes; Filter pore size: <5 μm.
[0033] 7. Drying step: Pre-freezing conditions: -30 °C, 2 hours; Vacuum environment: 0.01 MPa; Drying time: 10 hours.
[0034] 8. High-shear emulsification: Emulsification speed: 3000 rpm; Emulsification time: 30 minutes.
[0035] 9. Particle size and specific surface area control: Particle size: D90 ≤ 15 μm; Specific surface area: 7.9 m 2 / g.
[0036] Example 2: 1. Microbial culture: Fermentation strain: Bacillus, 3 parts are used.
[0037] Culture medium formula: Glucose: 25 parts; Ammonium chloride: 5 parts; Water: 120 parts; Inoculation amount: 6%.
[0038] Culture conditions: Temperature: 40 °C; pH: 7.5; Cultivation time: 45 hours.
[0039] 2. Fermentation broth collection: Centrifugation speed: 3500 rpm; Centrifugation time: 8 minutes; Filter membrane pore size: 0.50 μm.
[0040] 3. Natural organic matter extraction: Chitosan dosage: 15 parts; Water dosage: 90 parts; Extraction conditions:; Temperature: 80 °C; Extraction time: 1 hour; Filtration: Filter using a 150 - mesh filter cloth.
[0041] 4. Pretreatment of calcium carbonate powder and talc powder: Calcium carbonate powder and talc powder are mixed at a ratio of 1:1, with each at 60 parts; Sieving specification: 250 - mesh sieve.
[0042] Drying conditions: Temperature: 80 °C; Time: 7 hours.
[0043] 5. Composite treatment: Fermentation broth: 12 parts; Natural organic matter extract: 7 parts; Pretreated powder: 110 parts.
[0044] Reaction conditions: Temperature: 35 °C; Stirring rate: 250 rpm; Reaction time: 4 hours; pH: 6.5.
[0045] 6. Separation step: Centrifugation speed: 3500 rpm; Centrifugation time: 9 minutes; Filter pore size: < 5 μm.
[0046] 7. Drying step: Pre - freezing conditions: - 25 °C, 1 hour; Vacuum environment: 0.02 MPa; Drying time: 8 hours.
[0047] 8. High - shear emulsification: Emulsification speed: 3500 rpm; Emulsification time: 40 minutes.
[0048] 9. Particle size and specific surface area control: Particle size: D90 ≤ 15 μm; Specific surface area: 7.5 m 2 / g.
[0049] Example 3: 1. Microbial culture: Fermentation strain: Bacillus, 1 part is used.
[0050] Culture medium formula: Glucose: 18 parts; Ammonium chloride: 2 parts; Water: 105 parts; Inoculation amount: 4%.
[0051] Culture conditions: Temperature: 25 °C; pH: 6.8; Culture time: 55 hours.
[0052] 2. Fermentation broth collection: Centrifugation speed: 2800 rpm; Centrifugation time: 12 minutes; Filter membrane pore size: 0.40 μm.
[0053] 3. Natural organic matter extraction: Chitosan dosage: 6 parts; Water dosage: 95 parts.
[0054] Extraction conditions: Temperature: 65 °C; Extraction time: 3 hours; Filtration: Filter using a 180-mesh filter cloth.
[0055] 4. Pretreatment of calcium carbonate powder and talc powder: Calcium carbonate powder and talc powder are mixed in a ratio of 1:1, with each ratio being 50 parts; Sieving specification: 150-mesh sieve.
[0056] Drying conditions: Temperature: 70 °C; Time: 9 hours.
[0057] 5. Composite treatment: Fermentation broth: 8 parts; Natural organic matter extract: 3 parts; Pretreated powder: 90 parts.
[0058] Reaction conditions: Temperature: 28°C; Stirring rate: 180 rpm; Reaction time: 4 hours; pH: 6.9.
[0059] 6. Separation step: Centrifugation speed: 2700 rpm; Centrifugation time: 11 minutes; Filtration pore size: < 5 μm.
[0060] 7. Drying step: Pre-freezing conditions: -40°C, 3 hours; Vacuum environment: 0.01 MPa; Drying time: 12 hours.
[0061] 8. High-shear emulsification: Emulsification speed: 2700 rpm; Emulsification time: 25 minutes.
[0062] 9. Particle size and specific surface area control: Particle size: D90 ≤ 15 μm; Specific surface area: 7.8 m 2 / g.
[0063] Comparative Example 1: Compared with Example 1, the difference is that the specific surface area is 8.4 m 2 / g, exceeding the range of not exceeding 8 m 2 / g in the claims, and the rest are the same.
[0064] Comparative Example 2: Compared with Example 1, the difference is that stirring is cancelled during the reaction (stirring rate is 0 rpm), and no energy input is provided, and the rest are the same.
[0065] Comparative Example 3: Compared with Example 2, the difference is that chitosan is not added during the extraction of natural organic matter, that is, the key functional component is removed, and the rest are the same.
[0066] Comparative Example 4: Compared with Example 2, the difference is that the reaction pH is set to 8.2, exceeding the range of pH 6 - 7 defined in the claims, and the rest are the same.
[0067] Comparative Example 5: Compared with Example 3, the difference is that the pre-freezing conditions are not set, and directly enter the drying stage, and the rest are the same.
[0068] Comparative Example 6: Compared with Example 3, the difference is that the particle size D90 is 18 μm, exceeding the range of D90 ≤ 15 μm in the claims, and the rest are the same.
[0069] Comparative experiment: Purpose of the experiment: To evaluate the influence of different formulation parameters on the performance of the final product.
[0070] Experimental procedures: 1. Sample preparation: Prepare various powder samples according to the parameter settings of Examples 1-3 and Comparative Examples 1-6.
[0071] Ensure that except for the variables, the rest of the processes and raw materials are the same.
[0072] 2. Adsorption efficiency test: Add the powder sample into the target solution, and set the concentration and stirring time.
[0073] Take the supernatant, and determine the change in the concentration of the target substance by ultraviolet spectrophotometer or titration method.
[0074] Calculate the adsorption rate: ; 3. Dispersibility test: Add the sample into the liquid dispersion system, use ultrasonic assistance and then observe after standing.
[0075] Give a dispersibility score of 0-10 (the higher the better) through visual scoring, optical microscopy or laser particle size analyzer.
[0076] 4. Degree of agglomeration evaluation: Use electron microscopy or visual observation method to evaluate whether obvious agglomeration occurs after dry powder or liquid dispersion, and classify it into three categories: "low / medium / high".
[0077] 5. Sedimentation rate test: Disperse the sample and then let it stand, record the change in the sinking mass or volume per unit time, and convert the sedimentation rate (mg / min) (the experimental results are shown in the following table).
[0078] Comparative table of experimental results It can be seen from the above table that: The experimental results show that the product performance is highly sensitive to key parameters in multiple dimensions, which can be explained from the perspectives of material structure regulation and surface interface interaction. The specific surface area and particle size directly determine the contact interface size between the material and the target medium and the exposure degree of active sites. When the specific surface area exceeds the set threshold (such as Comparative Example 1), it may cause an enhanced tendency of agglomeration and deformation of the micro-pore structure, resulting in uneven adsorption; while too large particle size (such as Comparative Example 6) will reduce the interface reaction efficiency and dispersion stability, increase the sedimentation rate, verifying the importance of controlling the particle size within 15 μm.
[0079] From the perspective of the composite process, energy input (such as stirring and pre-freezing) plays a decisive role in the stable construction of the structure. Without stirring (Comparative Example 2), it will lead to uneven material distribution, affecting the synergistic effect of the composite reaction; the absence of the pre-freezing step (Comparative Example 5) will destroy the crystal template effect in freeze-drying, affecting the maintenance of the microchannels and specific surface area. This is consistent with the "freezing-deconstruction-shaping" synergistic mechanism we proposed, that is, only by providing energy drive during the gradual construction of the structure can an ideal porous network be formed and its spatial structure be stabilized.
[0080] In terms of functional components and reaction conditions, the absence of chitosan (Comparative Example 3) makes it impossible for natural organic matter to effectively form a complex structure during the composite process, reducing the adsorption function and surface activity; while when the pH exceeds the limit value (Comparative Example 4), it will break the charge balance in the microenvironment, resulting in unstable composite deposition or reaction stagnation. This indicates that the construction of materials not only depends on the components themselves, but is also significantly affected by the interfacial electrochemical environment, further verifying the rationality and necessity of the "bio-chemical double synergistic construction mechanism" we proposed previously.
[0081] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for compound modification of calcium carbonate powder and talcum powder, characterized in that, It includes the following steps: S1. Cultivate microorganisms capable of secreting bioactive substances to obtain the fermentation products required for modification; S2. Collect the cultured fermentation broth to provide bio-assisted modification components; S3. Extract natural organic matter to be used as a modification adjuvant; S4. Pretreat calcium carbonate powder and talc powder; S5. Compound the fermentation broth, natural organic matter and the pretreated powder, and carry out a modification reaction; S6. Separate and remove residual microbial impurities to obtain a pure composite product; S7. Dry the composite product to obtain the final composite modified powder.
2. A method for compound modification of calcium carbonate powder and talcum powder according to claim 1, characterized in that The cultivation steps of the microorganisms include: Select 1-3 parts by weight of Bacillus strains as fermentation strains; The components contained in the culture medium are formulated according to the following parts by weight: 15-25 parts of glucose, 2-5 parts of ammonium chloride, and 100-120 parts of water; The inoculation amount is 3-7% of the total amount of the culture system; Control the culture temperature at 20-40 °C, the pH value at 6.5-7.5, and the culture time at 45-55 hours.
3. A method for compound modification of calcium carbonate powder and talc powder according to claim 1, characterized in that, The collection steps of the fermentation broth include: Centrifuge at 2500-3500 rpm for 8-12 minutes to remove the bacterial cells; Take the supernatant and filter it through a 0.35-0.55 μm microporous filter membrane; Retain the filtrate as the subsequent modification component.
4. A method for compound modification of calcium carbonate powder and talc powder according to claim 1, characterized in that The extraction steps of the natural organic matter include: Select 5-15 parts of chitosan as the natural organic matter; Add the natural organic matter to 90-100 parts of water and extract it at 60-80 °C for 1-3 hours; Filter it through a 150-250 mesh filter cloth and use it for the compound reaction.
5. A method for compound modification of calcium carbonate powder and talc powder according to claim 1, characterized in that, The pretreatment steps of the calcium carbonate powder and talc powder include: Mix the calcium carbonate powder and talc powder according to a mass ratio of 1:1, and the mixing ratio is 50-60 parts each; Sieve it through a 150-250 mesh sieve; Dry it at 70-80 °C for 7-9 hours until the moisture content < 1%.
6. A method for compound modification of calcium carbonate powder and talcum powder according to claim 1, characterized in that, The compound treatment steps include: Mix 8-12 parts of the fermentation broth, 3-7 parts of the natural organic matter extract, and 90-110 parts of the pretreated calcium carbonate-talc mixed powder; Stir and react in a reaction kettle under normal pressure conditions, the reaction temperature is 25-35 °C, the stirring rate is 150-250 rpm, the reaction time is 2-4 hours, and the pH value is controlled at 6-7.
7. A method for compound modification of calcium carbonate powder and talcum powder according to claim 1, characterized in that, The separation steps include: Centrifuge at 2500-3500 rpm for 8-12 minutes to remove the residual microorganisms in the reaction; Further filter it using a filter cloth, and the filtration pore size < 5 μm; Collect the solids in the filtrate as the composite product.
8. A method for compound modification of calcium carbonate powder and talcum powder according to claim 1, characterized in that, The drying steps include: Adopt the freeze-drying method; Pre-freeze at -25 to -40 °C for 1-3 hours; Dry it in a vacuum environment of 0.01-0.02 MPa for 8-12 hours to obtain the dried composite powder.
9. A method for compound modification of calcium carbonate powder and talcum powder according to claim 1, characterized in that, The composite reaction is carried out by mixing with a high-shear emulsifier, the emulsification speed is 2500-3500 rpm, and the emulsification time is 20-40 minutes.
10. A method for composite modification of calcium carbonate powder and talcum powder according to claim 1, characterized in that, The particle size of the composite modified powder is controlled such that D90 ≤ 15 μm, and its specific surface area > 8 m 2 / g.
